Revising Mariametridae: the genera Dichrometra, Lamprometra, and Liparometra (Echinodermata: Crinoidea). Issue 2 (17th February 2018) - Taylor, Kristian H.; Rouse, Greg W.; Messing, Charles G.
Abstract : The featherstar genera, Dichrometra A.H. Clark, 1909a, Lamprometra A.H. Clark, 1913, and Liparometra A.H. Clark, 1913 (Comatulida: Mariametridae), are currently diagnosed only on the basis of the relative lengths of their proximal three pairs of pinnules. Previous published descriptions and a morphological re-examination indicate that this character is inconsistent and phenotypically variable. Distinctions amongst most of the 11 currently recognized species within each of these three genera are similarly ambiguous. This study compared currently accepted diagnostic characters amongst members of these three genera and incorporated mitochondrial DNA and nuclear DNA sequencing to assess taxonomic distinctions. Specimens were obtained from throughout the range of all three genera. Molecular data supported a monophyletic grouping, which we have placed under the senior generic name Dichrometra, based on a level of intraspecies divergence similar to that in other featherstar taxa, with four distinct species-level clades: palmata Müller, 1841, flagellata Müller, 1841, gyges Bell, 1884, and brachypecha H.L. Clark, 1915, the latter two resurrected from synonymy under palmata . Amongst these, proportions of proximal pinnules contributed only to the diagnosis of D. brachypecha . These species and the genus are redescribed. However, new diagnostic morphological characters remain, because they are needed to corroborate the four clades distinguished by molecular data. Because no sequence data were available from specimens identifiable as the remaining nine nominal species, we maintain them as accepted, pending further information.